Spirits in the city: the changing structure of Zhong Yuan Jie in Singapore from 1965-2000 - Lim, Ting Xuan (Nanyang Technological University, 2023)
The Hungry Ghost Festival in Singapore is one of the most celebrated festivals amongst the Chinese. However, the socioeconomic climate in Singapore have influenced the changes in religious practice. The essay exemplifies these changes through the study of three temples in Singapore: 修德善堂养心社 Seu Teck Sean Tong Yiang Sin Sia, 正龙宫玄江殿Chia Leng Kong Heng Kang Tian Temple, and 沙岡萬山福德祠Sar Kong Mun San Fook Tuck Chee. The study of these temple elucidated how socioeconomic policies influenced changes in traditional temple rituals. These temples are forced to change due to the lack of availability of traditional ritual offerings. Yet, these temples attempted to hold on to their traditional practices in spite of these changes. Therefore, the material culture of these food and paper offerings, along with the rituals conducted, have continued to shift their meaning due to the changing socioeconomic context of Singapore.